2017
DOI: 10.1155/2017/5146723
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa Responsive Parkinsonism in Patients with Hemochromatosis: Case Presentation and Literature Review

Abstract: Hemochromatosis is an autosomal recessive disorder which leads to abnormal iron deposition in the parenchyma of multiple organs causing tissue damage. Accumulation of iron in the brain has been postulated to be associated with several neurodegenerative diseases including Parkinson's disease. The excess iron promotes Parkin and α-synuclein aggregation in the neurons. Excess iron has also been noted in substantia nigra on MRI especially using susceptibility weighted imaging in patients with Parkinson's disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Hereditary haemochromatosis (HH) was also frequently identified in this systematic review. Four papers reported typical Parkinsonism [ 31 , 32 , 33 , 34 ] while atypical features were described in the remaining three papers. All papers were related to unresponsiveness to levodopa [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hereditary haemochromatosis (HH) was also frequently identified in this systematic review. Four papers reported typical Parkinsonism [ 31 , 32 , 33 , 34 ] while atypical features were described in the remaining three papers. All papers were related to unresponsiveness to levodopa [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rare reports of parkinsonian syndrome in hereditary hemochromatosis describes characteristic symptoms of resting tremor, bradykinesia, rigidity, and an asymmetric onset. Mixed resting and action tremor were also reported in one patient case ( 27 29 ).…”
Section: Inherited Metabolic Disordersmentioning
confidence: 66%
“…As previously discussed, the dysregulation of iron metabolism has been suggested to contribute to the risk of PD development. This is further evidenced through the observation of altered iron levels in the SNpc of PD patients through MRI findings and postmortem samples ( 27 , 123 125 ). Increased intracellular iron promotes the degeneration of dopaminergic neurons via several suggested pathways, in addition to the enhancement of oxidative stress as previously described ( 53 ).…”
Section: Inherited Metabolic Disordersmentioning
confidence: 94%
See 1 more Smart Citation
“…However, toxic effects of paraquat are attenuated by the conjugation of free radical metabolites with glutathione-S-transferases [61]. Studies on the patients with PD revealed high iron level in substantia nigra, where iron accumulation is associated with C282Y mutations responsible for hemochromatosis, a hereditary iron overload disorder than the controls, suggesting C282Y mutation increases the risk of PD [62]. Further, redox activity in neuromelanin-aggregates is significantly higher in the PD patients manifested by severe neuronal loss, may be due to severe oxidative stress [63].…”
Section: Toxicants and Oxidative Stress In Pdmentioning
confidence: 99%